GAMBARAN TINGKAT PENGETAHUAN SISWA KELAS XI TERHADAP BAHAYA PENYALAHGUNAAN OBAT TRAMADOL DI SMK “X” DI KABUPATEN KUNINGAN - Imas Maesaroh; Retina Aghistni Rahmawati (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2018)
Tramadol is one of the drugs that is often misused by students or adolescents. Tramadol belongs to the peripheral analgesic group as a pain reliever and is obtained by prescription. Tramadol has an euphoria ef ect and causes dependence. One of the causes of drug abuse is lack of knowledge. This research was conducted with the aim to know the level of knowledge of class XI students against the dangers of drug abuse Tramadol in one of Vocational High School in Kuningan District. The research design used was descriptive quantitative research, with sampling using purposive sampling technique. Data collection was done by using questionnaire instrument. Of the 96 respondents, the average percentage of Students' Level of Class XI Knowledge on the Danger of Tramadol Drug Abuse in SMK